The archaeology of caves in Ireland - Dowd, Marion (Oxbow Books, 2015)
"This book provides a synthesis of what we currently know about how caves were used and perceived by communities spanning the 10,000 years of human occupation of Ireland, from the earliest Mesolithic hunter gatherers to the 21st century urban dweller"--Provided by publisher.